Waste to animal feed - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
Currently, Food Waste (FW) is a pressing global issue with significant environmental, social, and economic implications. According to the Food and Agriculture Organization (FAO), approximately one-third of all food produced for human consumption ― almost 1.3 billion tons globally ― is lost or wasted each year . This wastage occurs throughout the food system, from farm to fork. However, FW in high-income countries mainly originates from food consumption whereas in low-income countries it comes from food production and food processing [1]. This reflects differences in consumers' habits and behavior and in the technological underpinnings of local food systems. Regardless of which part of the food system FW originates from, it has serious consequences for food security [2], resource conservation [3], and climate change [4]. FW contributes to greenhouse gas emissions through various processes. Greenhouse gases, such as carbon dioxide and methane, are emitted when FW is landfilled [5]. The total global amount of FW generates 3.3 billion tons of carbon dioxide emission annually [6]. Landfilling also contributes to the formation of leachate, a toxic liquid that can contaminate groundwater and surface water.